On the development of heavy and fast scintillation nano-ceramics; IEEE Nuclear Science Symposium Conference Record, 2008. NSS '08, Dresden, october 19-25, 2008 - Borisevich A.; Dosovitsky A.; Fedorov A.; Khasanov O. L. Oleg Leonidovich; Korzhik M.; Mechinsky V.; Missevitch O.; Shevchenko G. (2008, 2008)
Combination of nano-crystalline compounds allows to achieve ceramic composites which never can be obtained in a single crystalline or micro ceramic transparent body. In particular, combination of nano-particles of fast, bright but lightweight scintillator and heavy radiator in a single transparent composite becomes possible. Here we compare scintillation properties of YAG:Ce, YAG:Ce/HfO2(Y), YAG:Ce/Lu203, LuAG:Ce/Lu 203 nano-ceramics. Prospects of their application in PET detector modules solely or in combination with LSO:Ce, LuYAP:Ce etc. are discussed